ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERSEDIAAN DAN KETERAKSESAN INTERNET FINANCIAL REPORTING OLEH PEMERINTAH DAERAH - Wau, Ikhlas; Ratmono, Ratmono (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to analyze factors affecting availability and accessibility of Government’s internet financial reporting (IFR). Factors which are going to be tested are political competition, local government’s size, local government’s financial independency, income per capita and audit opinion. This study examines 112 local government on Java Island based on availability and accessibility from its website. This study tested by two methods, ordinal regression method for the availlability and multiple regression method for the accessibility. The study using ordinal regression found that income per capita and audit opinion has positive relationship to the availability of financial information on the Government’s website. The study using multiple regression found that local government’s financial independency has positive relationship to the accessibility of financial information in Government’s website.